2021
DOI: 10.3390/cancers13020182
|View full text |Cite
|
Sign up to set email alerts
|

Bromamine T (BAT) Exerts Stronger Anti-Cancer Properties than Taurine (Tau)

Abstract: Background: Taurine (Tau) ameliorates cancer pathogenesis. Researchers have focused on the functional properties of bromamine T (BAT), a stable active bromine molecule. Both N-bromotaurine (TauNHBr) and BAT exert potent anti-inflammatory properties, but the landscape remains obscure concerning the anti-cancer effect of BAT. Methods: We used Crystal Violet, colony formation, flow cytometry and Western blot experiments to evaluate the effect of BAT and Tau on the apoptosis and autophagy of cancer cells. Xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The therapeutic efficacy as well as the anti-tumour or anti-cancer properties of bromamine-T and taurine were established, when they were found to inhibit the growth of colon, breast, cervical, as well as skin cancer cells. 22 Marcinkiewicz and co-workers found that bromamine-T (BAT) exhibit potent microbicidal activity against yeasts and bacteria. They found that BAT exhibits better activity than taurine bromamine (Tau-NHBr) for treatment of infectious diseases associated with inflammatory response.…”
Section: Biological Significance Of Bromamine-tmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic efficacy as well as the anti-tumour or anti-cancer properties of bromamine-T and taurine were established, when they were found to inhibit the growth of colon, breast, cervical, as well as skin cancer cells. 22 Marcinkiewicz and co-workers found that bromamine-T (BAT) exhibit potent microbicidal activity against yeasts and bacteria. They found that BAT exhibits better activity than taurine bromamine (Tau-NHBr) for treatment of infectious diseases associated with inflammatory response.…”
Section: Biological Significance Of Bromamine-tmentioning
confidence: 99%
“…The therapeutic efficacy as well as the antitumour/anticancer properties of bromamine-T and taurine were established after they were found to inhibit the growth of colon, breast, cervical, and skin cancer cells. 22…”
Section: Biological Significance Of Bromamine-tmentioning
confidence: 99%
“…BAT has been illustrated to exert anti-inflammatory and anti-microbial effects to a similar extent as those of TauNHBr (38). In particular, BAT retains potent anti-microbial, anti-inflammatory and anti-cancer potential in vitro (38,40). The anti-inflammatory effect of BAT is mediated by reducing the protein expression levels of TNF-α, IL-6 and IL-12p40, with its most prominent effect emerging in the inhibition of IL-12p40 protein expression, as confirmed by enzyme-linked immunosorbent assay (ELISA) experiments (38).…”
Section: Bromamine T a Stable Active Bromine Compound Prevents The Lps-induced Inflammatory Responsementioning
confidence: 99%
“…Taurine, in most cells, can be transported into cells via a sodium/chloridedependent symporter, SLC6A6 36 . A few recent reports provided evidence that taurine supplementation suppresses the growth of colon, cervical and endometrioid cancer cells [37][38][39] ; however, the role of taurine in OC growth suppression is poorly understood.…”
Section: Introductionmentioning
confidence: 99%